Petrogenesis and tectonic significance of the ~850 Ma Gangbian alkaline complex in South China: Evidence from in situ zircon U-Pb dating, Hf-O isotopes and whole-rock geochemistry - Li, X.; Li, W.; Li, Q.; Wang, Xuan-ce; Liu, Y.; Yang, Y. (Elsevier Science BV, 2010)
The Gangbian alkaline complex in the southeastern Yangtze Block (South China) is composed of Si-undersaturated pyroxene syenites and Si-saturated to -oversaturated syenites and quartz monzonites. SIMS zircon U–Pb analyses indicate that the complex was emplaced at 848 ± 4 Ma, during a previously-recognized interval of magmatic quiescence between the ca 1.0–0.89 Ga Sibaoan orogenic magmatism and the ca 0.83–0.78 Ga magmatic flare-up. The Gangbian rocks are characterized by wide, coherent variations in major and trace elements (SiO2 = 47.6–68.4%, K2O + Na2O = 4.5–10.5%, K2O/Na2O = 0.4–1.2, MgO = 1.2–8.5%, Cr = 4.5–239 ppm, and Ni = 4.5–143 ppm) and by enrichment in LIL and LREE and depletion in Nb, Ta and P in trace element spidergrams. Their whole-rock εNd(T) (− 6.5 to − 0.4) and εHf(T) (− 10.7 to 0.4) are positively correlated, suggesting involvement of both metasomatized mantle and continental crust materials in their genesis. In situ zircon Hf–O isotopic measurements for the most evolved quartz monzonite sample yield a binary mixing trend between the mantle- and supracrustal-derived melts.It is suggested that the pyroxene syenites were derived by partial melting of metasomatized, phlogopite-bearing lithospheric mantle, and the parental magma experienced extensive fractionation of pyroxene and olivine associated with varying degrees of crustal contamination. Subsequent fractional crystallization of hornblende and minor amounts of plagioclase from the alkali basaltic magmas, accompanied by crustal contamination, produced the Si-saturated to -oversaturated syenites and quartz monzonites. These ca. 0.85 Ga alkaline rocks and neighboring contemporaneous dolerite dykes are the products of the anorogenic magmatism after the Sibao Orogeny. They post-date the final amalgamation between the Yangtze and Cathaysia Blocks, most likely manifesting the initial rifting of South China within the Rodinia supercontinent.